2021
DOI: 10.15587/1729-4061.2021.227984
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of logarithmic transformation function to expand the range of high-precision measurements

Abstract: Studies of the effect of normalized radiation fluxes on the measurement result revealed the most influential one. The value of the normalized flow F0 was shown to have a greater effect on the relative measurement error than ΔF0. This allows investigating the relationship between the controlled Fx and the normalized flow F0. Experimental studies have confirmed that by a threefold increase in the normalized flow F0 relative to the controlled flow Fx, it becomes possible to increase the measurement accuracy in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A study was conducted to determine the influence of values of normalized values T 0 and ∆T on the measurement result over the entire range of measured temperatures T x . This does not differ from the approaches that were reported in [20], in which regularities between normalized and sought values were also taken into account. As a result, it was established (Table 1) that the value of the relative error decreases when the value of the normalized temperature T 0 increases and remains constant when the values of the normalized temperature ∆T change.…”
Section: Discussion Of Results Of Computer Modeling With a Cubic Tran...mentioning
confidence: 62%
See 1 more Smart Citation
“…A study was conducted to determine the influence of values of normalized values T 0 and ∆T on the measurement result over the entire range of measured temperatures T x . This does not differ from the approaches that were reported in [20], in which regularities between normalized and sought values were also taken into account. As a result, it was established (Table 1) that the value of the relative error decreases when the value of the normalized temperature T 0 increases and remains constant when the values of the normalized temperature ∆T change.…”
Section: Discussion Of Results Of Computer Modeling With a Cubic Tran...mentioning
confidence: 62%
“…This circumstance is due to the fact that in order to introduce redundancy, it is necessary to form value-normalized physical quantities of the same physical nature as the measuring one. Therefore, in work [20] regularities between normalized and sought values were established, which leads to the expansion of the range of high-precision measurements. The expediency of using redundant methods is also confirmed by their application with a quadratic sensor transformation function [21].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Processing of measurement results in accordance with the proposed equations provides automatic exclusion of the additive and multiplicative components of the error, i.e. error correction, which does not contradict the data presented in [19][20][21][22][23][24][25]. In addition, due to the application of the proposed redundant measurement equations ( 11) and ( 14), it is possible to directly use a nonlinear TF without special measures for its linearization, which are typical for studies published in [12][13][14].…”
Section: Discussion Of the Results Of Computer Modeling Of The Quadra...mentioning
confidence: 79%
“…However, the issue of the influence of the values of normalized quantities and their relationship with the desired quantity on the final measurement result for a nonlinear transformation function remains unresolved. Therefore, further research on redundant measurement methods presented in [25] established a relationship between the normalized and desired quantities, which significantly expands the range of high-precision measurements. The results obtained demonstrated the high efficiency of redundant measurement methods in improving measurement accuracy by adjusting the values of normalized quantities for the logarithmic transformation function.…”
Section: Due To This It Can Be Argued On the Use Of Non-precision Nor...mentioning
confidence: 99%
“…It is shown that this allows increasing the accuracy of measurements by eliminating the systematic component of the error due to changes in the parameters of the transformation function, as well as reducing the random component of the error. Redundant measurements with a nonlinear transformation function were further developed in [19]. It is shown that due to the regularity between the normalized and sought quantities, the range of high-precision measurements is significantly expanded.…”
Section: To This When Applying the Second Approach It Becomes Possibl...mentioning
confidence: 99%